Visiting the “enemy”: visitation in politically unstable destinations - Farmaki, Anna; Antoniou, Katerina; Christou, Prokopis A. (My University, 2019)
Purpose – This study aims to examine the factors shaping the intentions of people to visit a hostile outgroup. Design/methodology/approach – An exploratory, qualitative research approach was followed. Specifically, 77 semi-structured interviews with citizens of the divided island of Cyprus were conducted. Findings – This study identifies several categories of visitors and non-visitors, depicted along a continuum, and concludes that there is a multiplicity of factors in the socio-political environment which influence the travel intentions of people. Originality/value – This study not only imparts insights into the way travel decision-making evolves in politically unstable situations but also serves as a stepping stone towards understanding the conditions under which reconciliation between hostile nations may be encouraged by travel.
Keywords: Tourism; Travel intentions; Political instability; Reconciliation